Clinicopathological study and molecular subtyping of muscle-invasive bladder cancer (MIBC) using dual immunohistochemical (IHC) markers - R. Vaithegi; Kanthilatha Pai; Anuradha Calicut Kini Rao; Vidya Monappa; Swathi Prabhu; Nischitha Suvarna (Diagnostic Pathology)
Abstract Background Muscle-invasive bladder carcinomas (MIBCs) exhibit significant heterogeneity, with diverse histopathological features associated with varied prognosis and therapeutic response. Although genomic profiling studies have identified several molecular subtypes of MIBC, two basic molecular subtypes are identified - luminal and basal, differing in biological behaviour and response to treatment. As molecular subtyping is complex, surrogate immunohistochemical (IHC) markers have been used to determine the molecular subtypes with good correlation to genomic profiling. Methods We analysed the clinicopathological features of 66 cases of MIBCs received over a 5-year study period. IHC expression was determined using GATA3 and CK5/6 to classify MIBC into luminal, basal and double-negative subtypes. The association between clinicopathologic variables and molecular subtypes were analysed using Chi-square test. Results The mean age at diagnosis of MIBC was 65.91 years with a male predominance. Based on IHC expression of GATA3 and CK5/6, MIBCs were classified into luminal, basal and double negative subtypes in 62.1%, 30.3% and 7.6% respectively. The luminal subtype occurred at an older age and showed predominantly conventional urothelial carcinoma with papillary morphology. Basal subtype occurred at earlier age, showed greater association with smoking and was more commonly associated with urothelial carcinoma with non -papillary morphology and exhibiting divergent differentiation as well as pure squamous cell carcinoma on histopathological examination. The double-negative subtype was found exclusively in males and exhibited a non-papillary morphology. Notably, all diagnosed neuroendocrine carcinomas were classified as double-negative type. While there was no statistically significant difference in tumour stage in cystectomy specimens between the molecular subtypes, lympho-vascular invasion and lymph node metastasis was more commonly associated with the basal type (p < 0.05) There was no significant difference in recurrence rates, metastasis and death between luminal and basal subtypes. Conclusion A simple two-antibody panel using GATA3 and CK5/6 could help in classifying MIBC into basic molecular subtypes of MIBC with distinctive histopathological features that can provide insights into the corresponding molecular subtype. Greater association of lymphovascular invasion and lymph nodal involvement in cystectomy specimens in basal type and distant metastasis in the double-negative subtype suggests a more aggressive clinical behaviour of these, necessitating more intensive treatment.